The Purpose of India's Security Strategy : Defence, Deterrence and Global Involvement - Sen, Gautam (London Routledge, 2020)
This book comprises the journey of the Indian nation state and its tryst with destiny, where successive political leaderships, while governing India, contributed to a better understanding of the idea of India, its political and strategic culture, and the role that its military has had to play to develop that culture.
Include Bibliography
Keywords: National security -- India -- Military policy -- Security, International -- Military relations -- Deterrence (Strategy)